→ Mnożenie jednomianów przez sumy algebraiczne ←

Uzupełnij:
a) .........-2ab² : 8 = 2ab - .......
b) kn(......... - n) = -k²n - ........
c) ......... × (3xy - 2t) = 6x²y - .......
d) ½a(4a²b² - ......_ = ...... - a³
e) 3y² + ........ : (-6) = .......... - ⅓

Wygląda, że jest trudne ale nie jest ;)

1

Odpowiedzi

Najlepsza Odpowiedź!
2010-03-02T17:33:40+01:00
A) 2ab - 2ab² :8= 2ab - ¼ab²
b) kn( -k - n)= -k²n - kn²
c) 2x ×( 3xy - 2t)= 6x²y - 4xt
d)½a(4a²b²- 2a²) =2a³b² - a³
e)3y²-(-2 ): (-6)= 3y² -⅓